STUDY THE INDONESIAN LANGUAGE TEXTBOOK CLASS X INDEPENDENT CURRICULUM PUBLISHED BY YUDHISTIRA - Regita Amelia; Sabrina Pramesuary; Dwi Nanda; Yulisin Nazra; Inayah Hanum; Safinatul Hasanah Harahap (Indonesian language and literature education program Majapahit Islamic University, 2024)
This research aims to determine (1) the suitability of the content, (2) the suitability of the language, and (3) the suitability of presenting the Indonesian language textbook, namely